Carnitine-acylcarnitine translocase deficiency: a case report with autopsy - Chennakeshava Thunga; Suvradeep Mitra; Devi Dayal; Sadhna Lal (University of São Paulo, 2024)
Fatty acid oxidation defects are a heterogeneous group of disorders related to the mitochondrial fatty acid oxidation pathway. Carnitine acylcarnitine translocase (CACT) is an enzyme responsible for the unidirectional transport of acylcarnitine across the inner mitochondrial membrane. This enzyme plays a crucial role in the oxidation of fatty acids. The autopsy pathology of the CACT deficiency is described in only a few cases. We describe the autopsy pathology of a child with CACT deficiency dominantly in the form of microvesicular steatosis of the hepatocytes, renal proximal tubular epithelia, cardiac myocytes, and rhabdomyocytes. The diagnosis was further confirmed on whole exome sequencing with compound heterozygous variants in the exon 1 (c.82G>T, p.Gly28Cys; likely pathogenic) and exon 5 (c.535G>A, p.Asp179Asn; uncertain significance) of the SLC25A20 gene. This case elucidates the histopathology of the liver and the detailed autopsy of a case of CACT deficiency from India.